Analyzing the Implementation of the Public Utility Vehicle Modernization Program (PUVMP) to the Employment of PUV Drivers in the Philippines - Malasique, Arion Mari P.; Windsor Redz C. Rubio, Windsor Redz C.; Rosete, Marie Antoinette L. (Journal of Industrial Engineering & Management Research, 2022)
With the traditional ways of public transportation in the Philippines, the current transportation system has been deemed inconvenient to daily commuters and public utility operators - traffic congestion, lack of public vehicles for commuters resulting into longer transportation time and hassle rides, and the environmental problems that arises in the continuity of using polluting gas are the main reasons as to why Filipinos continue to demand for a better transport system. The rise of modern transportation promises effective solutions to address the recurring problem stated above. This study examines the implementation of the Public Utility Vehicle Modernization Program (PUVMP) on the employment of PUV drivers, especially the small operators who do not have the capacity to upgrade their vehicles. With the goal of the proposed program, this study aims to analyze and determine the significant effect of PUVMP to the employment of PUV drivers in the Philippines. The employment of PUV drivers decreased because of the ongoing health crisis, and there was a significant difference in the number of traditional PUV units since the modernized units are inadequate